Effect of Quality of Work Life, Motivation, and Reward on the Performance of Inpatient Nurses at the Regional General Hospital dr. Zubir Mahmud IDI, East Aceh Regency in 2021 - Malinda, Risnati (Budapest International Research and Critics University, 2022)
This study aims to determine effect of quality of work life, motivation, and reward on the performance of inpatient nurses at the Regional General Hospital dr. Zubir Mahmud IDI, East Aceh Regency in 2021. This research method is analytic with a cross sectional design using primary data obtained from filling in using a questionnaire with a sample of 54 respondents using a total sampling technique. Data was bivariate analysis with chi-square test. The results showed that there was a relationship between quality of work life on the performance of inpatient nurses (p-value=0.002 < a=0.05). There is a relationship between motivation on the performance of inpatient nurses (p-value=0.000 < a=0.05). There is a relationship between reward on the performance of inpatient nurses (p-value=0.006 < a=0.05).